1999
DOI: 10.1182/blood.v94.9.2945
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity to Complement and a Decreased Red Blood Cell Life Span in Mice Mosaic for a Nonfunctional Piga Gene

Abstract: The gene PIGA encodes one of the protein subunits of the 1-6-N acetylglucosaminyltransferase complex, which catalyses an early step in the biosynthesis of glycosyl phosphatidylinositol (GPI) anchors. PIGA is somatically mutated in blood cells from patients with paroxysmal nocturnal hemoglobinuria (PNH), leading to deficiency of GPI-linked proteins on the cell surface. To investigate in detail how inactivating mutations of the PIGA gene affect hematopoiesis, we generated a mouse line, in whichloxP-mediated exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 36 publications
5
40
0
Order By: Relevance
“…2 B shows the relative level of PIGA − cells for all four blood cell lineages and the proportion of PIGA − reticulocytes measured at the age of 4 (45%, 34–57%), 8 (53%, 24–74%), and 16 (66%, 33–97%) mo. The proportion of PIGA − red blood cells was significantly lower than PIGA − reticulocytes in all animals analyzed, which is consistent with the shortened half-life of PIGA − red cells in circulation 22. We have previously shown that PIGA − red cells from mice mosaic for a nonfunctional Piga gene have an increased sensitivity to complement 22.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…2 B shows the relative level of PIGA − cells for all four blood cell lineages and the proportion of PIGA − reticulocytes measured at the age of 4 (45%, 34–57%), 8 (53%, 24–74%), and 16 (66%, 33–97%) mo. The proportion of PIGA − red blood cells was significantly lower than PIGA − reticulocytes in all animals analyzed, which is consistent with the shortened half-life of PIGA − red cells in circulation 22. We have previously shown that PIGA − red cells from mice mosaic for a nonfunctional Piga gene have an increased sensitivity to complement 22.…”
Section: Resultssupporting
confidence: 83%
“…The proportion of PIGA − red blood cells was significantly lower than PIGA − reticulocytes in all animals analyzed, which is consistent with the shortened half-life of PIGA − red cells in circulation 22. We have previously shown that PIGA − red cells from mice mosaic for a nonfunctional Piga gene have an increased sensitivity to complement 22. Similarly, also PIGA − red cells from LF mice showed an increased lysis when exposed to complement (data not shown), suggesting that the decreased half-life of PIGA − red cells is due to the action of complement.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The mechanism for the expansion is unknown. Nevertheless, both in vitro culture of normal and Pig-a knockout (KO) mouse embryonic stem (ES) cells and in vivo study by generation of Pig-a KO chimaeric mice observed no growth advantage of the abnormal ES cells over the normal cells (Dunn et al, 1996;Kawagoe et al, 1996;Lin et al, 1998;Tremml et al, 1999).…”
mentioning
confidence: 99%